2020
DOI: 10.1155/2020/9483670
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Properties of a Bacterial Endophyte, Methylobacterium radiotolerans MAMP 4754, Isolated from Combretum erythrophyllum Seeds

Abstract: is study reports on the isolation and identification of Methylobacterium radiotolerans MAMP 4754 from the seeds of the medicinal plant, Combretum erythrophyllum, for the purposes of investigating antimicrobial and antioxidant activities from this endophyte. e strain identity was confirmed by 16S rRNA-based phylogeny and Scanning Electron Microscopy (SEM). Ethyl acetate and chloroform (1 : 1 v/v) extracts from the endophyte were tested for antimicrobial and antioxidant activity on a total of 7 bacterial species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 69 publications
(74 reference statements)
0
31
0
1
Order By: Relevance
“…The MIC and MMC of A. pluriseta solvent fractions were analyzed as previously described [ 36 , 57 , 60 , 61 , 63 ]. Briefly, 50 μL of varying fraction concentrations (3.9–500 μg/mL petroleum ether, dichloromethane, and methanol; 1.95–250 μg/mL ethyl acetate) were added into 100 μL of nutrient broth held in a sterile 96-well plate followed by addition of 50 μL test organisms adjusted to 0.5 McFarland standard.…”
Section: Methodsmentioning
confidence: 99%
“…The MIC and MMC of A. pluriseta solvent fractions were analyzed as previously described [ 36 , 57 , 60 , 61 , 63 ]. Briefly, 50 μL of varying fraction concentrations (3.9–500 μg/mL petroleum ether, dichloromethane, and methanol; 1.95–250 μg/mL ethyl acetate) were added into 100 μL of nutrient broth held in a sterile 96-well plate followed by addition of 50 μL test organisms adjusted to 0.5 McFarland standard.…”
Section: Methodsmentioning
confidence: 99%
“…This antibiofilm effect has also been described in other rapidly growing non-tuberculous mycobacteria, such as Mycobacterium abscessus , Mycobacterium fortuitum , and Mycobacterium chelonae [ 35 ]. This antibacterial effect has been described in other Methylobacterium strains, for instance, the ERI-135 strain isolated from the soil whose ethyl acetate extract inhibited the growth of bacteria such as Bacillus subtilis , Klebsiella pneumoniae , Pseudomonas aeruginosa , Salmonella typhimurium , Shigella flexneri , Enterobacter aerogenes , Staphylococcus aureus and S. epidermidis and fungi, such as Candida albicans and Trichophyton rubrum [ 38 ]; the Methylobacterium radiotolerans MAMP 4754 isolated from the seeds of the river bushwillow ( Combretum erythrophyllum (Burch.) Sond), whose ethyl acetate and chloroform extracts also showed antibacterial effect on B. subtilis, B. cereus, Escherichia coli, K. oxytoca, and Mycobacterium smegmatis [ 40 ]; and Methylobacterium extorquens DSM13060, an intracellular meristem endophyte of scots pine ( Pinus sylvestris L.), whose defensin-like antimicrobial peptide MB1533 showed an inhibitory effect on S. aureus and B. subtilis [ 37 ].…”
Section: Discussionmentioning
confidence: 82%
“…Methylobacterium is a genus from Alphaproteobacteria isolated by Patt et al [ 34 ] that is a strictly aerobic bacterium and forms small rose colonies at its optimal growth temperature (25 °C) and usually inhabits water distribution systems [ 32 , 35 ]. Some strains of Methylobacterium genus have already demonstrated antibacterial effect against different microorganisms, both Gram-positive and Gram-negative bacteria [ 36 , 37 , 38 ], including mycobacteria [ 33 ], and fungi [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sy et al [ 87 ] isolated Bacillus indicus HU36, producing carotenoids from human fecal and assessed the stability (sensitivity to iron-induced autoxidation) and antioxidant activity (inhibition of iron-induced lipid peroxidation). Photolo et al [ 88 ] reported Methylobacterium radiotolerans MAMP 4754 (IC 50 of 5.65 μg/mL) contains 9-octadecene, 2,4-dinitrophenyl acetate, and 2(5H)-furanone that can scavenge ROS [ 88 ]. Violacein, a purple pigment is a potent antioxidant primarily produced by Chromobacter violaceum and Pseudoalteromonas , stimulating mucosal defense mechanisms for protection against oxidative damage due to gastric ulcers [ 34 ].…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%
“…Whenever there is a discussion about fungal metabolites, the story of penicillin has been told many times. Alexander Fleming, in 1929 discovered that mold juice’ from Penicillium notatum had antibacterial action and named this biological activity “Penicillin” [ 88 ]. In the past few years, researchers instigated to look for a fungal strain that could be grown quickly and produce bioactive metabolites in submerged culture.…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%